Social and Economic Democracy and Removal of Untouchability (Global Journal of Human-Social Science, 2012)
Ambedkar viewed democracy as an instrument of bringing about change peacefully Democracy does not merely mean rule by the majority or government by the representatives of the people This is a formalistic and limited notion of democracy Like many other national leaders Ambedkar had complete faith in democracy Ambedkar made ceaseless efforts for the removal of untouchability and the material progress of untouchables From 1924 onwards he led the movement of untouchables till the end of his life He firmly believed that the progress of the nation could not be realized without first removing untouchability Ambedkar held the view that the removal of untouchability was linked to the abolition of the caste system and that it could be only by discarding the religious notions from the basis of the caste system Therefore in the course of his analysis of the caste system he examined the Hindu religious philosophy and criticized it He did this boldly often facing strong resentment from the orthodox Hindus This paper attempts to investigate Ambedkar s thought on democracy and removal of untouchability For this the researcher discuss about social and economic democracy factors necessary for the successful operation of democracy removal of untouchability self-respect among untouchables and some of the important factors like education economic progress political strength conversion
Keywords: Democracy; Social Thought; Political Thought; Untouchability